State of Placentas in Pregnant Rats After Implantation of Cryopreserved Allogenic Placental Fragments - Kuzmina, Irina Yu.; Kuzmina, Olga A.; Gubina-Vakulik, Galyna I.; Dobrunova, Iryna V. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2): 151–155<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />